Infrared spectroscopic anaylsis of polymorphism in diphenyl carbazide - El-Kabbany, F.; Hassan, S. Taha; Hafez, M. (Univerzita Pardubice, 2010)
Infrared (IR) analysis is used here to investigate the changes in N-N, N-H, and C=O bonds of thermally treated diphenyl carbazide (DPC) during the variation from room temperature up to 160 oC. Polymorphism in the DPC compound has been studied by detecting the changes in some IR spectroscopic parameters (e.g., mode shift, band contour) during the elevation of temperature. Beside IR spectroscopy, also differential scanning calorimetry, X-ray diffraction, NMR, and atomic mass spectra were used as supplementary identification techniques. All of the vibrations of DPC were found to be due to the ionic fundamentals 3311 cm–1, 3097 cm–1, 3052 cm–1, 1677 cm–1, 1602 cm–1, 1492 cm–1, 1306 cm–1, 1252 cm–1, 887 cm–1 and 755 cm–1. The results revealed for the first time that the thermally treated DPC traverse four different phase transformations at 50, 90, 125, and 140°C. The crystal structure was found to be amorphous, monoclinic, tetragonal, 58 El-Kabbany F. et al./Sci. Pap. Univ. Pardubice Ser. A 16 (2010) 57–73 orthorhombic and amorphous in the temperature range of 30-160 °C. The X-ray diffraction patterns support the results obtained by IR.
Keywords: infrared analysis; polymorphism; diphenyl carbazide